A learning community approach to identifying interventions in health systems to reduce colorectal cancer screening disparities - Man, Lillian C. (Prev Med Rep, 2018)
Although colorectal cancer (CRC) screening in the United States has been increasing, screening rates are not optimal, and there are persistent disparities in CRC screening and mortality, particularly among minority patients. As most CRC screening takes place in primary care, health systems are well-positioned to address this important population health problem. However, most health systems have not actively engaged in identifying and implementing effective evidence-based intervention strategies that can raise CRC screening rates and reduce disparities. Drawing on the Collective Impact Model and the Interactive Systems Framework for Dissemination and Implementation, our project team applied a learning community strategy to help two health systems in southeastern Pennsylvania identify evidence-based CRC screening interventions for primary care patients. Initially, this approach involved activating a coordinating team, steering committee (health system leadership and stakeholder organizations), and patient and stakeholder advisory committee to identify candidate CRC screening intervention strategies. The coordinating team guided the steering committee through a scoping review to identify seven randomized trials that identified interventions that addressed CRC screening disparities. Subsequently, the coordinating team and steering committee applied a screening intervention classification typology to select an intervention strategy that involved using an outreach strategy to provide minority patients with access to both stool blood test and colonoscopy screening. Finally, the coordinating team and steering committee engaged the health system patient and stakeholder advisory committee in planning for intervention implementation, thus taking up the challenge of reducing and important health disparity in patient populations served by the two health systems.